Financial Health Analysis of PT Bank Muamalat Indonesia Tbk. for the Period 2019–2024 Using the Altman Z-Score and Springate S-Score Models - Mutmainah, Arofiani; Sugianto; Nurlaila (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the financial health of PT Bank Muamalat Indonesia Tbk. during 2019–2024 by comparing the modified Altman Z-Score and Springate S-Score models. Using annual financial statements, this study applies a quantitative descriptive-comparative approach to calculate financial ratios and bankruptcy prediction scores. The findings show improved financial performance since late 2021, reflected in stronger working capital, operating profit, and equity. However, both models produce different signals regarding financial distress risk. These results highlight the importance of using multiple analytical tools as an early warning system and suggest improving profitability, asset efficiency, and capital strength. Keywords: Financial Health; Altman Z-Score; Springate S-Score; Bank Muamalat; Financial Distress